Analysis of Proof of Testimonium de Auditu in Cases of Moral Violations - Ismawati Septiningsih (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Witness testimony is a crucial piece of evidence in proving the occurrence of a criminal act. Witnesses as people who see, hear and experience a criminal incident themselves are very effective in the process of proving criminal cases. The weakness is that not all cases have enough witnesses who saw, heard and experienced the criminal incident. Rape cases, for example, are known only to the victim and the perpetrator. This article will discuss the evidentiary power of testimonium de auditu witnesses who did not see, hear or experience a criminal incident themselves. This research was conducted through a case study approach. The results of this research are that the information provided by the testimonium de auditu witness has evidentiary power as long as it does not conflict with the statements of other witnesses and other evidence.